2017
DOI: 10.1155/2017/6404918
|View full text |Cite
|
Sign up to set email alerts
|

Corneal Nerve Regeneration after Self-Retained Cryopreserved Amniotic Membrane in Dry Eye Disease

Abstract: Purpose To evaluate the efficacy of self-retained cryopreserved amniotic membrane (CAM) in promoting corneal nerve regeneration and improving corneal sensitivity in dry eye disease (DED). Methods In this prospective randomized clinical trial, subjects with DED were randomized to receive CAM (study group) or conventional maximum treatment (control). Changes in signs and symptoms, corneal sensitivity, topography, and in vivo confocal microscopy (IVCM) were evaluated at baseline, 1 month, and 3 months. Results Tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
41
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 38 publications
(45 citation statements)
references
References 54 publications
3
41
1
Order By: Relevance
“…Furthermore, use of cAM for NK is further supported by two recent studies, in which PKS was shown to promote corneal nerve regeneration in patients with severe dry eye disease and concurrently reduce corneal neuropathic pain. 37,38 These findings may shed light on the successful outcomes observed in this retrospective series, which predominantly comprised corneal ulcers with underlying NK. Further prospective studies are warranted to confirm our findings.…”
Section: Discussionmentioning
confidence: 56%
“…Furthermore, use of cAM for NK is further supported by two recent studies, in which PKS was shown to promote corneal nerve regeneration in patients with severe dry eye disease and concurrently reduce corneal neuropathic pain. 37,38 These findings may shed light on the successful outcomes observed in this retrospective series, which predominantly comprised corneal ulcers with underlying NK. Further prospective studies are warranted to confirm our findings.…”
Section: Discussionmentioning
confidence: 56%
“… 23 Such anti-inflammatory action exerted by CAM is retained in the water-soluble extract 24 , 25 and replicated by HC-HA/PTX3 purified from AM. 11 , 12 A third mechanism is CAM’s ability to regenerate corneal nerves as previously reported, 7 , 26 and this may explain the lasting effect. This notion is supported by the fact that NGF is abundantly present in CAM and is known to play an important role in nerve regeneration and epithelial healing.…”
Section: Discussionmentioning
confidence: 80%
“…Cryopreserved amniotic membrane (CAM) was used to treat DED with ocular surface involvement, and its short-term efficacy was attributed to its known potent anti-inflammatory effect. 6 More recently, John et al 7 further evaluated the potential effect of CAM in restoring corneal nerves in DED using in vivo confocal microscopy due to the known correlation between corneal nerve density and the severity of DED. 8 10 They showed CAM treatment significantly increased corneal nerve density which was correlated with improved corneal sensitivity and reduced dry eye symptoms.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…160,161 One retrospective review by Macdonald et al 162 applied AMT for 5.4 (±2.8 days) on average with a sustained reduction in the DED marker (3.25±0.5 to 1.47±0.6) three months post operatively with improvement in both patient reported symptoms and clinical signs. Finally, other authors report how corneal nerve density can be significantly improved following AMT application, 163 potentially accelerating the recovery of the ocular surface health in patients with DED.…”
Section: Dry Eye Disease (Ded)mentioning
confidence: 97%